Burkina Faso : Staff Report for 2009 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility, and Requests for Augmentation of Access and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2010)
In 2008-09, economic activity in Burkina Faso was negatively affected by the increase in global food and fuel prices, the global economic and financial crisis, and heavy flooding in Ouagadougou in September 2009. These shocks are estimated to have contributed to a deterioration in poverty indicators. Spending on emergency and humanitarian needs rose after the 2009 flooding. Fiscal stimulus measures were also adopted to support economic activity. Executive Directors have welcomed the authorities' resolve to enhance revenue performance and expenditure management while unwinding exceptional expenditure generated by adverse exogenous shocks.